2023
DOI: 10.3390/vetsci10020106
|View full text |Cite
|
Sign up to set email alerts
|

Development of a TaqMan-Probe-Based Multiplex Real-Time PCR for the Simultaneous Detection of African Swine Fever Virus, Porcine Circovirus 2, and Pseudorabies Virus in East China from 2020 to 2022

Abstract: African swine fever virus (ASFV), porcine circovirus 2 (PCV2), and pseudorabies virus (PRV) are important DNA viruses that cause reproductive disorders in sows, which result in huge losses in pig husbandry, especially in China. The multiplex qPCR assay could be utilized as a simultaneous diagnostic tool for field-based surveillance and the control of ASFV, PCV2, and PRV. Based on the conserved regions on the p72 gene of ASFV, the Cap gene of PCV2, the gE gene of PRV, and the porcine endogenous β-Actin gene, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Cellular immune responses may be nonspecific but enhance host resistance, confirming the excellent applicability of SC as a probiotic. The invasion and proliferation of pathogenic bacteria contribute to host death after ASFV infection ( 70 , 71 ). Therefore, enhancing host immune resistance can reduce ASFV invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immune responses may be nonspecific but enhance host resistance, confirming the excellent applicability of SC as a probiotic. The invasion and proliferation of pathogenic bacteria contribute to host death after ASFV infection ( 70 , 71 ). Therefore, enhancing host immune resistance can reduce ASFV invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the single detection methods used in other studies, the multiplex PCR method showed higher specificity and sensitivity, allowing for the simultaneous detection of multiple pathogens in a single reaction. This approach not only saves time and resources, but also facilitates the rapid identification of various pathogens in complex samples ( Liu et al, 2023 ). Our multiplex fluorescent quantitative PCR assays demonstrated high specificity, sensitivity, and efficiency in detecting respiratory pathogens, such as SARS-CoV-2, FluA, PIV, and RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these highly sensitive assays can lead to false positives due to cross-contamination and false negatives due to the presence of inhibitors or damaged nucleic acids. Therefore, novel PCR assays, which were developed by redesigning the primer sequence or forming a multiplex assay to improve efficacy and reduce processing time, showed higher sensitivity, specificity, and efficiency than those previously used globally [109][110][111][112][113][114]. Wang et al added a new set of primers and probes, which cover the 5 end region of p72, leading to potent diagnostic sensitivity and specificity; the limit of detection (LOD) was six copies of positive standard plasmids per reaction, or about 0.1-1 TCID 50 of ASFV isolates per reaction, and ASFV was well distinguished from nontargeted common swine virus [109].…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%